English Online Class: Evaluation and Students’ Learning Boredom - Zulfa, Puspa Fortuna; Galuhwardani, Cindyra; Tazali, Imam (English Education and Literature Journal (E-Jou), 2024)
English online class has been conducted as a variety of language learning. It is also as an implementation of the advance of technology and educational system in post pandemic era. This study aimed at investigating English online class as an evaluation and describing students’ learning boredom appeared during class. It employed students majoring Information System and Accounting Information System to ask for their ideas, perception and complains by spreading questionnaires and open-ended interview. The data gathered were analyzed by describing and interpreting them qualitatively. It resulted that English online class could be implemented as a new way of learning and there was learning boredom had by students with some factors, internally and externally.